Development and validation of the Benzodiazepine Hypnotics Withdrawal Symptom Scale (BHWSS) based on item response theory. (June 2021) - Narisawa, Hajime; Inoue, Yuichi; Kobayashi, Mina; Okajima, Isa; Kikuchi, Takashi; Kagimura, Tatsuo; Matsui, Kentaro; Inada, Ken; Mishima, Kazuo
Highlights: We refined and validated the Benzodiazepine Hypnotics Withdrawal Symptom Scale. Item response theory was used for developing the scale. The 10-item revised version of the scale has sufficient reliability and validity. Abstract: This study aimed to refine and validate the Benzodiazepine Hypnotics Withdrawal Symptom Scale (BHWSS). The 12-item prototype version of the BHWSS was administered to a sample of 346 patients with chronic insomnia (161 males and 185 females, mean age: 52.8 ± 16.6 years) who had been taking hypnotics (benzodiazepines [BZDs] or BZD receptor agonists) for at least 3 months. The item information curve indicated that two of the 12 BHWSS items should be excluded. As a result of analyzing the 10-item version of the BHWSS (revised-BHWSS), the contribution rate in the case of the factor 1 was 0.49, Cronbach's α was 0.90, and the reliability coefficient ω was 0.91. An analysis of the item information curve for the revised-BHWSS indicated that the information amount per item increased from 3.90 for the original 12-item BHWSS to 4.37 for the 10-item revised-BHWSS. The receiver operating characteristic curve indicated that 6.5 points on the revised-BHWSS was the most appropriate cutoff for estimating moderate or severe withdrawal symptoms using the Benzodiazepine Dependence Self-Report Questionnaire as a reference. These results suggest that the 10-item revised-BHWSS has sufficient reliability and validity for evaluating the severity of withdrawal symptoms after discontinuing BZDs.